TUTORING AS THE PEDAGOGICAL TECHNOLOGY FOR THE DEVELOPMENT OF RESEARCH SKILLS IN LANGUAGE STUDENTS - Sergeeva, Marina; Poliakova, Iana; Petrova, Marina; Martynova, Anastasiya; Jiuyan, Gao; Anran; Antonella, Selvitella (Revista Inclusiones, 2020)
Traditional approaches to teaching and learning do not meet the modern requirements for the pedagogical process and professional competencies of a teacher. New methods and forms of training are being developed, which are regarded as a compulsory component of education, endowing it with specific features. Such a situation necessitated the emergence of the broad concept “pedagogical technology”, which came into wide use at the turn of the millennium. A broad scope of interpretations indicates the lack of integration of this concept into modern scientific usage, despite the significant demand for the corresponding notion in the theory of education. It is in this context that the term “technology” and the complex terms derived from it (“teaching technologies”, “pedagogical technologies”, etc.) began to be actively used in theoretical literature in a variety of combinations, depending on the perception of the structure and components of the educational process by a particular author. Despite the fact that the tutor’s profession is relatively new to Russian education, the demand for the services of such specialists is growing steadily. The modernized educational environment requires a new type of professional, capable to help the students to plan their own educational program. Tutoring support for the development of students’ research skills meets the needs of the target audience and the requirements for the individualization of higher education.